Characterisation of Two Wood-Waste and Coffee Bean Husk Biochars for the Removal of Micropollutants from Water - Van Limbergen, Thessa; Roegiers, Inez Henriette; Bonné, Robin; Mare, Federica; Haeldermans, Tom; Joos, Bjorn; Nouwen, Olivier; Manca, Jean V.; Vangronsveld, Jaco; Thijs, Sofie (Frontiers in Environmental Science, 2022)
The inclusion of bioaugmented low-cost biochar in current wastewater treatment technologies is a promising way to enhance the removal and degradation of emerging contaminants. In this paper, the properties of three wood waste biochars (coffee bean husks - COF, wood waste mix - AB, and date palm fiber wood - PDF), produced at four temperatures (350°C, 450°C, 500°C, 550°C) were compared, and investigated in the presence of Geobacter sulfurreducens or a mixed freshwater stream bacterial culture to understand their potential for the adsorption and biotransformation of two types of pesticides (thiacloprid, pirimicarb), and two pharmaceuticals (ibuprofen, diclofenac). Biochar yield was similar for all three biochars and ranged between 30-35%. The ash content of PDF and COF was significantly higher than AB. pH and electrical conductivity (EC) were initially high for COF (pH: 7.4-8; EC: 3-4.27 mS/cm) and PDF (pH: 7.7-10.1; EC: 4-6.24 mS/cm) after 24h, but stabilized at neutral pH and < 0.5 mS/cm EC after additional washes. COF and AB did not leach high concentrations of chloride (< 10 mg/l), nitrate (<1 mg/l) , nor sulphate (<76 mg/l), this in contrast to date palm fiber wood (PDF) with 1760 mg/l Cl- (550 °C), and 846 mg/l sulphate (350°C). Lower pyrolysis temperatures reduced leachable anions. The biochars were highly (ultra)microporous with little meso- and macroporosity. The adsorption experiments showed that AB and COF biochars were both suited to sorb more than 90 % of the initially spiked 10 ppm pirimicarb, AB removed 50.2 % of the initial diclofenac concentration compared to only 5 % for the no-biochar control, and both biochars could remove about 55 % of the initially spiked thiacloprid, and 40 % of the ibuprofen. In the presence of a mixed culture, on average 30 % more thiacloprid and ibuprofen was removed from the supernatant by AB and COF than the sterile control. This work shows that selected wood-waste feedstocks and low pyrolysis temperature can produce environmentally-safe biochars that have suitable characteristics to sorb emergent pollutants from water. These materials could be further studied in multi-pollution sorption/competition experiments, and in larger environmental wastewater treatment systems.